Efficacy and Safety of Dulaglutide by Baseline HbA1c in Chinese Patients with Type 2 Diabetes: A Post Hoc Analysis - Yu, Miao (Diabetes Ther, 2020)
INTRODUCTION: To evaluate the efficacy and safety of dulaglutide 0.75 and 1.5 mg in patients with type 2 diabetes mellitus (T2DM) by baseline glycated hemoglobin (HbA1c) < 8.5% or ≥ 8.5% after 26 weeks of treatment. METHODS: Assessment of the Weekly AdministRation of dulaglutide in Diabetes (AWARD) China 1 (CHN1) study (NCT01644500, n = 556) included patients on dulaglutide vs. glimepiride who were treatment naïve or on monotherapy but discontinued therapy. AWARD-CHN2 (NCT01648582, n = 591) patients were on dulaglutide vs. insulin glargine and continued on metformin and/or sulfonylurea. Mean daily dose of glimepiride and insulin glargine was 2.51 mg and 21.0 IU, respectively. Post hoc analyses were conducted based on mixed-model repeated measures using a modified intent-to-treat analysis set with only the Chinese population. Change from baseline in HbA1c and body weight was analyzed by individual study. RESULTS: In the two studies, 70.1% of patients in AWARD-CHN1 and 59.7% in AWARD-CHN2 had baseline HbA1c < 8.5% (mean HbA1c 7.4% and 7.6%, respectively) and 29.9% in AWARD-CHN1 and 40.3% in AWARD-CHN2 had baseline HbA1c ≥ 8.5% (mean HbA1c 9.2% and 9.4%, respectively). In AWARD-CHN1, the HbA1c reductions at 26 weeks with baseline HbA1c < 8.5% and ≥ 8.5%, respectively, were dulaglutide 1.5 mg: − 1.1% and − 2.2%; dulaglutide 0.75 mg: − 0.9% and − 2.0%; glimepiride: − 0.7% and − 1.4%. In AWARD-CHN2, the HbA1c reductions at 26 weeks with baseline HbA1c < 8.5% and ≥ 8.5%, respectively, were dulaglutide 1.5 mg: − 1.2% and − 2.3%; dulaglutide 0.75 mg: − 1.0% and − 1.7%; and insulin glargine: − 0.6% and − 1.7%. Irrespective of baseline HbA1c, body weight decreased with both dulaglutide doses and increased with either glimepiride or insulin glargine at 26 weeks. Dulaglutide demonstrated low incidence of hypoglycemia in both doses in the two trials. Hypoglycemia incidence was generally lower in patients with baseline HbA1c ≥ 8.5%. CONCLUSIONS: Dulaglutide demonstrated significantly greater HbA1c reduction with weight loss and lower risk of hypoglycemia compared with active comparators in Chinese patients with T2DM irrespective of baseline HbA1c, with much greater HbA1c reductions in patients with a higher baseline HbA1c. TRIAL REGISTRATION: ClinicalTrials.gov identifier, NCT01644500 and NCT01648582. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13300-020-00804-2) contains supplementary material, which is available to authorized users.